Estudo da Cinética da Sorção de Cromo Hexavalente por Biomassa Fúngica de Aspergillus ochraceus - Costa Sá, Laion Mairton; Orlanda, José Fábio França (Orbital: The Electronic Journal of Chemistry, 2015)
In this study we evaluated the ability of sorption of fungal biomass of Aspergillus ochraceus removal of hexavalent chromium in aqueous medium. The experiments were performed at pH 2 contact time 72 hours, 100 mg of fungal biomass and the equilibrium concentration ranging from 5,0 to 50,0 mg L-1. The results showed that the Freundlich model set to the best experimental data showing high coefficient of Freundlich (Kf = 486,2) and favorably 1/n value, indicating a very high sorption capacity. The biomass showed the presence of polysaccharides, hydroxylated groups, carboxylate and amino able to positively influence the kinetics of biosorption as this may increase the contact surface of the biomass with the molecule of Cr(VI). The results showed that biomass of Aspergillus ochraceus has the potential to be used in industrial wastewater treatment systems. DOI: http://dx.doi.org/10.17807/orbital.v7i4.727